INTEGRATION OF ISLAMIC ECONOMICS AND MSME DIGITALIZATION AS A STRATEGY TO ACHIEVE ECONOMIC INCLUSION WITHIN THE SDGS FRAMEWORK - Titania Diana Putri; Ruslan Abdul Ghofur; Budimansyah Budimansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study examines the integration of Islamic economics and the digitalization of Micro, Small, and Medium Enterprises (MSMEs) as a strategic approach to achieving economic inclusion within the framework of the Sustainable Development Goals (SDGs). The rapid advancement of digital technologies has transformed business ecosystems globally, offering new opportunities for MSMEs to enhance efficiency, expand market access, and improve financial management. Simultaneously, Islamic economics provides an ethical and justice-oriented foundation that promotes transparency, equitable distribution, and financial inclusion through Sharia-compliant principles. By combining these two frameworks, this study explores how digital innovation and Islamic values can jointly support inclusive and sustainable economic growth. Using a qualitative descriptive approach, data were sourced from academic journals, institutional reports, and policy documents to analyze the impact of digital transformation and Islamic economic practices on MSME development. The findings reveal that the adoption of digital tools such as e-commerce platforms, digital payments, accounting applications, and Islamic fintech significantly enhances MSME competitiveness and financial accessibility. Furthermore, Islamic financial instruments based on profit-and-loss sharing, fairness, and risk-sharing offer ethical alternatives that support business resilience and long-term sustainability. The integration of Islamic economics and digitalization aligns strongly with SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure), demonstrating its potential to advance inclusive economic participation, especially among marginalized groups. The study concludes that a synergistic approach combining digital transformation and Islamic economic principles is essential for building an equitable and resilient economic system. It recommends strengthening cross-sector collaboration, enhancing digital and financial literacy, and expanding access to Sharia-compliant digital infrastructure to maximize the inclusive impact of MSMEs in the digital era.